2019
DOI: 10.18332/tid/111397
|View full text |Cite
|
Sign up to set email alerts
|

Pro-tobacco marketing and anti-tobacco campaigns aimed at vulnerable populations: A review of the literature

Abstract: INTRODUCTIONWe reviewed research literature on pro-tobacco marketing and anti-tobacco campaigns targeting eight vulnerable populations to determine key findings and research gaps. Results can inform tobacco policy and control efforts and the design of public education campaigns for these groups.METHODSFive journal databases in medicine, communication, and science, were used to identify 8875 peer-reviewed, original articles in English, published in the period 2004–2018. There were 144 articles that met inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 162 publications
(185 reference statements)
2
50
1
Order By: Relevance
“…language or visual characteristics of intervention materials) and deep level cultural traits (e.g. familismo and simpatía) (Cruz et al 2019;Graham et al 2012;Russo et al 2018). Future tobacco control education campaigns targeting Latinos may benefit from incorporating this study's findings of the misconceptions about e-cigarette use being less harmful than other tobacco products to themselves and their family members.…”
Section: Study Implicationsmentioning
confidence: 90%
See 3 more Smart Citations
“…language or visual characteristics of intervention materials) and deep level cultural traits (e.g. familismo and simpatía) (Cruz et al 2019;Graham et al 2012;Russo et al 2018). Future tobacco control education campaigns targeting Latinos may benefit from incorporating this study's findings of the misconceptions about e-cigarette use being less harmful than other tobacco products to themselves and their family members.…”
Section: Study Implicationsmentioning
confidence: 90%
“…First, our findings corroborate that tobacco control initiatives should be tailored to US Latinos with an emphasis on socio-cultural traits that distinguishes them from other populations. For example, the collectivist nature of the Latino family system has been shown to be an important component of tobacco control interventions targeting Latinos (Cruz et al 2019;Graham et al 2012;Russo et al 2018). More specifically, recruitment strategies that include familismo contribute to increased participation in cigarette smoking cessation interventions through messaging oriented on benefits for the family, particularly the younger generations (Cruz et al 2019;Graham et al 2012;Russo et al 2018).…”
Section: Study Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19] A 2019 review indicated that rural residents in the USA were exposed to greater pro-tobacco advertising that appealed to cultural standards within rural communities. 20 Antitobacco media campaigns, especially localised messages on print, were reportedly received by rural communities with high reception. 20 Limited access to healthcare may also contribute to fewer opportunities for professional advice and support to quit smoking.…”
Section: Open Accessmentioning
confidence: 99%